PTU-046 A Retrospective Comparison of Plastic, Uncovered and fully Covered Metal Stents in the Management of Distal Malignant Biliary Strictures. (4th June 2013) - Sampaziotis, F; Evans, J; King, A; Macfarlane, B; Leahy, A
Abstract : Introduction: Uncovered self expanding metal stents (USEMS) are associated with longer patency and reduced complication rates compared to polyethylene stents (PS), for the management of distal malignant biliary strictures (DMBS) [1]. However, PS are used for unstaged tumours, due to difficulties in operative USEMS removal. Fully covered self expanding metal stents (FCSEMS) can be easily removed before or during surgical resection. Recent data supports their use as first line management of DMBS, regardless of resectability status [2]. The current study provides the first retrospective comparison of survival, patency and complication rates between PS, USEMS and FCSEMS in the context of DMBS. Methods: The records of all patients, who underwent endoscopic retrograde cholangiopancreatography and stent placement for newly diagnosed DMBS in our centre, between February 2007 and August 2012 were reviewed. Patients who subsequently underwent surgical resection were excluded from the patient survival estimation. The stent patency period was calculated as the period between stent insertion and occlusion; death or surgical resection with a patent stent. Cumulative patient survival and stent patency were estimated using the Kaplan Meier method. The log-rank test was used for comparison between groups. Fisher's exact test was used for comparison of complication rates. The statistical analysis software used was IBM SPSS Statistics 20. Results: 87 cases were identified: 37 PS (8.5 or 10 Ff), 26 USEMS (wallstent/wallflex) and 24 FCSEMS (wallflex). 7 patients proceeded to surgical resection. Stent occlusion occurred in 54%, 23% and 4.2% of the patients in the PS, USEMS and FCSEMS group respectively, with a mean patency period of 87, 144 and 196 days. Cumulative patency was higher in the FCSEMS vs USEMS group (p = 0.028) and higher in both groups compared to the PS group (p < 0.001 and p = 0.007 respectively) [Fig15 ]. No statistically significant difference was observed in survival or complications between the 3 groups. However, 6 episodes of cholangitis occured in the PS group vs 1 episode in each of the FCSEMS and USEMS groups; 2 episodes of pancreatitis were noted in the FCSEMS group vs none in the other groups. Conclusion: The use of FCSEMS as first line management for DMBS is associated with longer patency and similar complication rates compared to USEMS and PS. However, the risk of pancreatitis requires further assessment. Disclosure of Interest: None Declared References: Lammer J, et al. Common bile duct obstruction due to malignancy: Treatment with plastic versus metal stents. Radiology 1996; 201:167–72. Siddiqui AA, et al. Fully covered self-expandable metal stents are effective and safe to treat distal malignant biliary strictures, irrespective of surgical resectability status. J Clin Gastroenterol. 2011; 45:824–7.